Health Care in Saudi Arabia: A Sector in Transformation (The Review of Diabetic Studies, 2024)
Saudi Arabia’s health care system has undergone dramatic evolution over recent decades, driven by the government's devotion to community health and ambitious national development goals. The Kingdom's journey began in the mid-20th century, when health services were limited and concentrated primarily in major cities. Rapid population growth, urbanization, and rising expectations for quality of life fueled the need for a more organized and equitable system. Today, the health sector is a testament to decades of investment and reform. At its core, the system provides universal health coverage to Saudi citizens and residents, with the government offering free basic health care through extensive public networks while gradually expanding private sector participation. The rapid modernization of the sector reflects Saudi Arabia’s aspiration to become a regional leader in health outcomes and medical innovation.The Ministry of Health (MOH) remains the foundation of the system. It manages preventive, curative, and rehabilitative services across a vast network of primary health centers and specialized hospitals, using a referral system that connects local clinics to advanced care facilities.Under Vision 2030, health care has become a strategic sector for economic and social advancement. The government is investing heavily—an estimated $65+ billion—to modernize infrastructure, expand digital services like telemedicine, and reform financing and delivery systems through hospital clusters and private partnerships. Vision 2030 also aims to foster a vibrant research ecosystem and attract international medical partnerships. New policies have encouraged innovation in biotechnology, pharmaceuticals, and health education, positioning Saudi Arabia as a hub for clinical trials and medical research in the Middle East. These reforms are designed not only to improve patient care, but also to create high-value jobs and stimulate economic diversification beyond oil.